PSI-29 Impact of sociometric status on brush utilization in environmentally-enriched, feedlot steers. (5th December 2019) - Meneses, Xandra Christine A; Park, Rachel M; Daigle, Courtney L
Abstract: Environmental enrichment (EE) provides mental and physical stimulation to animals housed in captivity. Provision of brushes as EE allow cattle to perform diverse grooming behaviors, and previous research demonstrated that cattle engage in fewer stereotypic and aggressive behaviors when provided a brush. However, competition incited by a novel object may compromise animal welfare and prevent socially low-ranking individuals from using the brush. The objective of this study was to evaluate individual social relationships of feedlot cattle exposed to a brush as EE. Twenty-seven British and British-Continental crossbred steers were blocked by weight and assigned to three pens (n = 3 pens with 9 animals/pen), each containing an L-shaped, mounted brush. Video recordings were decoded from 0800 to 1730 for displacement frequency, as well as frequency and duration of brush usage on d 0, 1, 2, 4, 8, 16, 32, and 64 relative to brush implementation. A sociometric index was calculated for each individual by dividing the number of displacements initiated (Di ) by the number of displacements received (Dr ). A positive number indicated Di > Dr, and a negative number indicated Di < Dr . No linear or quadratic relationships (PROC REG) were observed between sociometric index and duration of brush usage (P > 0.05). Regardless of sociometric status, each steer had an equal opportunity to use and benefit from the cattle brush. EE efficacy is influenced by stocking density with the goal of each animal having the same level of access to a common resource, and this goal was achieved in this study. Displacement behaviors and sociometric indexes can be used as effective metrics to determine optimal stocking density in pens for EE and resource use.